Efficacy of Empagliflozin in patients with heart failure across kidney risk categories - Butler, Javed; Packer, Milton; Siddiqi, Tariq Jamal; Böhm, Michael; Brückmann, Martina; Januzzi, James L.; Verma, Subodh; Gergei, Ingrid; Iwata, Tomoko; Wanner, Christoph; Ferreira, João Pedro; Pocock, Stuart J.; et al. (Journal of the American College of Cardiology, 2023)
Background - Empagliflozin reduces the risk of major heart failure outcomes in heart failure with reduced or preserved ejection fraction. - Objectives - The goal of this study was to evaluate the effect of empagliflozin across the spectrum of chronic kidney disease in a pooled analysis of EMPEROR-Reduced and EMPEROR-Preserved (Empagliflozin Outcome Trial in Patients with Chronic Heart Failure with Reduced or Preserved Ejection Fraction, respectively). - Methods - A total of 9,718 patients were grouped into Kidney Disease Improving Global Outcomes (KDIGO) categories based on estimated glomerular filtration rate (eGFR) and urine albumin-to-creatinine ratio into low-, moderate-, high-, and very-high-risk categories, comprising 32.0%, 29.1%, 21.9%, and 17.0% of the participants, respectively. - Results - In the placebo arm, when compared with lower risk categories, patients at higher risk experienced a slower rate of decline in eGFR, but a higher risk of a composite kidney event. Empagliflozin reduced the risk of cardiovascular death or heart failure hospitalizations similarly in all KDIGO categories (HR: 0.81; 95% CI: 0.66-1.01 for low-; HR: 0.63; 95% CI: 0.52-0.76 for moderate-; HR: 0.82; 95% CI: 0.68-0.98 for high-; and HR: 0.84; 95% CI: 0.71-1.01 for very-high-risk groups; P trend = 0.30). Empagliflozin reduced the rate of decline in eGFR whether it was estimated by chronic slope, total slope, or unconfounded slope. When compared with the unconfounded slope, the magnitude of the effect on chronic slope was larger, and the effect on total slope was smaller. In EMPEROR-Reduced, patients at lowest risk experienced the largest effect of empagliflozin on eGFR slope; this pattern was not observed in EMPEROR-Preserved. - Conclusions - The benefit of empagliflozin on major heart failure events was not influenced by KDIGO categories. The magnitude of the renal effects of the drug depended on the approach used to calculate eGFR slopes.